GAMBARAN STATUS KARIES GIGI DAN KUALITAS HIDUP BERKAITAN DENGAN KESEHATAN GIGI DAN MULUT PADA NELAYAN DI KOTA MANADO - Rizka Wahyuni; Ni Wayan Mariati; Vonny Norry Sisca Wowor; Ni Made Nujita Mahartati; Virginia Eucharisty Wowor (JURNAL KEPERAWATAN, 2026)
Background: Dental caries is one of the most prevalent oral health issues. Untreated caries can lead to various complications that negatively impact an individual’s quality of life across physical, psychological, environmental, social, and spiritual dimensions. Objective: This study aims to describe the dental caries status and oral health-related quality of life (OHRQoL) among fishermen in Manado City. Methods: This quantitative study employed a cross-sectional design. Sampling was conducted using a purposive sampling method, involving 32 fishermen in Manado City as respondents. Dental caries status was measured using the DMF-T index, while the quality of life was assessed using the OHIP-14 questionnaire. Results: Among the 32 respondents, the majority (46.88%) fell into the "very high" category of the DMF-T index. Conversely, regarding oral health-related quality of life, most respondents (59.38%) were categorized as having a "good" quality of life based on the OHIP-14 scores. Conclusion: The majority of fishermen exhibited a very high prevalence of dental caries; however, their perceived quality of life remained in the good category.   Keywords: Dental Caries; Fishermen; Oral Health; Quality of Life